Perancangan Desain Karakter 2D Untuk Video Edukasi Rotasi Dan Revolusi Bumi - Yassinta Fitria; Rafif Virgian Darmanto; Widyasari Widyasari (Peneliti.net, 2023)
The Pandemic era had a significant impact on technological change. A lot of people have progressively used digital technology in the last few years. This increases the use of advanced technology such as gadgets, laptops, etc for educational purposes. Visual media that is equipped with audio such as Youtube has been the favorite media for alpha generation. Seeing the great opportunities in technology for the alpha generation, providing educational videos is considered quite effective and helpful, especially for elementary school children. Children will also be more interested in videos with interesting animated characters to make it easier for them to understand more about the discussion of related material than just audio which seems boring.